Characteristics of azimuthal anisotropy in SE Tibetan plateau and its relationship with the background of block structure - Liu, Jing; Wu, Jianping; Fang, Lihua; Chang, Kai; Yang, Ting; Wang, Changzai; Wang, Huaifu; Wang, Shuang (Frontiers in Earth Science, 2023)
The southeastern Tibetan Plateau, which straddles the Tibetan Plateau, Yangtze Block, and Cathaysia Block, is geotectonically situated in the compound part of the Tethys-Himalayan tectonic domain and the Peninsular Pacific tectonic domain. It is one of the critical regions for studying the scientific problems of plateau material lateral escape, lithosphere deformation, geotectonic properties of blocks, and deep dynamics. In this study, we use ambient noise data recorded by 401 broadband stations to obtain high-resolution short-period (T = 4–30s) Rayleigh wave azimuthally anisotropic phase velocity maps. These could provide fresh clues for an in-depth understanding of the crust-mantle velocity structure, deformation mechanism, and geotectonic evolution in the southeastern Tibetan Plateau. Within the Simao block, the strikes of the faults and the orientations of the principal compressive stress of the stress field both generally coincide with the fast-wave polarization direction (FPD). The FPD near the Lancangjiang fault zone in the west is in the NE-SW direction, near the Wuliangshan fault zone in the center is near the NS direction, and near the Red River fault zone in the east is the NW-SE direction. We estimate that the compressive stress in the southwest direction of the Tibetan Plateau material has a controlling effect on the crustal deformation of the Simao block, which is likewise blocked by the Lincang-Menglian granite belt, resulting in strong tectonic deformation. The FPD of the crust in the middle Red River fault zone is NS direction, significantly different from the fault strike. Combining with the seismic activity and GPS results, the depth of 8 km below the surface of the middle Red River fault is completely locked, and we conclude that the anisotropy of the upper crust of the middle part of the Red River fault zone is related to the action of the regional tectonic stress field. Taking into account geochemical and thermochemical results, we speculate that the complex tectonic stress at the junction of the blocks leads to prominent regional characteristics of the FPDs of azimuthal anisotropy in the crust, suggesting that the Shizong-Mile fault zone may be the western boundary between the Yangtze and Cathaysia blocks.